Las estructuras narrativas, desde la perspectiva de Gerard Genette, presentes en la obra “La Tregua” de Mario Benedetti - Leiva Solano, Margot Elizabeth (2018)
The present research work entitled: "The narrative structures, from the perspective of Gerard Genette, present in the work The Truce of Mario Benedetti", aims to explain and analyze the different events of diegesis in the work through the perspective proposed by Gerard Genette._x000D_ For the study, descriptive and analytical methods have been used to demonstrate the difference between history, story and narration. The most relevant conclusion reached is that the structures, according to Gerard Genette, serve to analyze a work in an accessible and understandable way.